Mediating Effect of Government Policies on Corporate Governance and Financial Performance of Savings And Credit Cooperative Societies in Uganda - Benon, Kyabarongo; Agaba, Moses; Jack , Rugasira (ADPEBI International Journal of Business and Social Science, 2025)
The purpose of this study was to investigate the effect of corporate governance on financial performance of SACCOs in Kiruhura District, Uganda and the specific objectives were;To examine the effect of board accountability on financial performance of selected SACCOs in Kiruhura District, In this study, a cross-sectional survey research design was employed, adopting quantitative and qualitative approaches research approaches. A total population of 342 people were used at a confidence level of 95% or error of 0.05 and the sample size was 184 respodents who involved the staff and members taken from the six SACCOs registered in Kiruhura districts, Uganda as of January 2023. the structural relationships between the variables in the suggested conceptual model were tested and examined using structural equation modeling (SEM). Jaffrey’s Amazing Statistical Program (JASP) version 0.17.2.0 was used to implement SEM. The findings of the study were: The effect of board accountability (BAC) on financial performance was found to have a negative effect.  Board risk management was found to have a significant positive influence on financial management of savings and credit co-operative societies (SACCOs).Board assurance  was found to have a significant positive influence on financial management of savings and credit co-operative societies (SACCOs).